2014
DOI: 10.1080/08905436.2014.931865
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Puffer Fish of the GenusLagocephalus: L. lunaris, L. spadiceusandL. inermis, Using Multiplex PCR

Abstract: A multiplex PCR assay was developed to identify widespread poison-containing puffer fishes of the genus Lagocephalus: L. lunaris, L. spadiceus and L. inermis, using a novel KUGEN_ILSspec primer set which is specific for 12S ribosomal RNA (12S rRNA) and Cytochrome b (Cyt b) genes. KUGEN_ILSspec set is composed of fish positive-amplified primers that produced a 289-bp fragment while L. lunaris-, L. spadiceus-and L. inermis-specific primers produced 123-, 196-and 493-bp fragments, respectively. The sensitivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The sensitivity of the developed multiplex PCR detected by capillary and agarose-based electrophoreses was 1 pg (Figures 4 and 5). Similar studies have reported a sensitivity of 5 ng for tuna and billfish and 1 ng for blowfish and freshwater fish species [26,37,38]. Our assay demonstrates better sensitivity than those in previously reported studies.…”
Section: Specificity and Sensitivity Of Multiplex Pcrsupporting
confidence: 74%
“…The sensitivity of the developed multiplex PCR detected by capillary and agarose-based electrophoreses was 1 pg (Figures 4 and 5). Similar studies have reported a sensitivity of 5 ng for tuna and billfish and 1 ng for blowfish and freshwater fish species [26,37,38]. Our assay demonstrates better sensitivity than those in previously reported studies.…”
Section: Specificity and Sensitivity Of Multiplex Pcrsupporting
confidence: 74%
“…This result indicated that the designed primers did not inhibit each other in a single reaction and had high specificity, resulting in the sensitivity that corresponded to that of the simplex PCR. Compared to the LOD of similar studies of fish products (5 ng for tunas and billfishes, 1 ng for freshwater fish species, and 1 ng for puffer fish), the LOD of our multiplex PCR assay (1 pg) is very sensitive and can detect very small amounts of cod DNA [21][22][23]. These results suggest that this PCR assay can be applied to on-site detection with low DNA extraction efficiency or to fragmented DNA samples such as processed food.…”
Section: Specificity and Sensitivity Of Multiplex Pcrmentioning
confidence: 77%
“…Furthermore, the position of the positive control PCR products on a gel image could be used as a secondary size reference of species-specific bands in addition to the primary size reference provided by the commercial DNA ladders (Figure 2 and 4). Despite the advantages of having the positive control primers in species identification using multiplex primer sets, there have been only a small number of reports that included them in the identification of food products (Catanese et al, 2010;Hellberg et al, 2010;Sangthong et al, 2014;Suwannarat et al, 2017), and in some meat and dairy products from farmed ruminants (Xue et al, 2017).…”
Section: Discussionmentioning
confidence: 99%